Tributyltin and Vascular Dysfunction: The Role of Oxidative Stress - Ronconi, Karoline de Sousa; Stefanon, Ivanita; Ribeiro Junior, Rogerio F. (Frontiers in Endocrinology, 2018)
The organotin compounds (OT) are used as fungicides, stabilizers in plastics, miticides, industrial and agricultural biocides, wood preserving and antifouling agents. Tributyltin (TBT) is a OT that was first used as an antifouling being the most effective agent used to prevent undesirable accumulation of marine organisms on solid surfaces, such as a ship’s hull or mechanical equipment, immersed in seawater. TBT can be easily absorbed by mammals, and its cytotoxic effects became a major concern since the discovery of the toxic effects in the years 70s. Recently, it has been demonstrated that TBT exposure have detrimental effect on the cardiovascular system. TBT is a membrane active molecule and its mechanism of action appears to be strongly dependent on the OT lipophilicity. As a result, TBT crosses the cell membrane and damages the endothelium and the smooth muscle cells. TBT exposure induces vascular dysfunction, most likely due to endothelial dysfunction and morphological changes in the vasculature wall. In experimental rodent model, small doses of TBT (100 and 500 ng/kg/bw/day for 15 days) can modify the vascular reactivity in aorta, mesenteric and coronary artery followed by smooth muscle cells atrophy, increased collagen deposition and fibrin accumulation. TBT exposure induces oxidative stress by increasing vascular superoxide anion production derived from NADPH oxidase and decreases nitric oxide (NO) production as well as eNOS protein expression. Thus, the aim of this review is to provide the current state of the art regarding the mechanisms involved in the vascular and endothelium dysfunction induced by TBT.